2019
DOI: 10.1097/md.0000000000015603
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological significance of Gamma-Glutamyltransferase in patients with hepatocellular carcinoma

Abstract: Background: Many studies explored the prognostic and clinicopathological significance of pretreatment serum Gamma-Glutamyltransferase (GGT) level in hepatocellular carcinoma (HCC). However, there are inconsistent results in the prognostic and clinicopathological significance of pretreatment serum GGT level in HCC. Thus, we conducted this meta-analysis to comprehensively assess the prognostic and clinicopathological significance of pretreatment serum GGT level in HCC patients. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…As an almost ubiquitous enzyme, γ-glutamyltransferase (γ-GT) initiates the degradation of extracellular glutathione and is also conjugates and correlates with biotransformation, nucleic acid metabolism, and oncogenesis [5]. Previous studies have shown that high levels of γ-GT are significantly associated with unfavorable prognoses in HCC patients [6, 7]. Prealbumin (PA), which is synthesized by the liver, is a recently identified biomarker indicative of liver synthetic functions and has not been included in the traditional Child-Pugh classification system.…”
Section: Introductionmentioning
confidence: 99%
“…As an almost ubiquitous enzyme, γ-glutamyltransferase (γ-GT) initiates the degradation of extracellular glutathione and is also conjugates and correlates with biotransformation, nucleic acid metabolism, and oncogenesis [5]. Previous studies have shown that high levels of γ-GT are significantly associated with unfavorable prognoses in HCC patients [6, 7]. Prealbumin (PA), which is synthesized by the liver, is a recently identified biomarker indicative of liver synthetic functions and has not been included in the traditional Child-Pugh classification system.…”
Section: Introductionmentioning
confidence: 99%
“…GGT is an enzyme which can be induced by intrahepatic obstruction or directly synthesized by liver cancer cells in HCC [26]. The diagnostic value of GGT has been deeply studied, and elevated GGT has been demonstrated to predict poor survival for HCC [27]. Accordingly, serum linc00152 and PTTG3P might be associated with the prognosis for HCC patients.…”
mentioning
confidence: 99%
“…9,14 AST trends upwards with increasing MTD, consistent with increased inflammation, as well as GGTP, which may also reflect hepatic inflammation, but is additionally reported as a candidate HCC biomarker. 15,16 Similarly, albumin trends downwards with increasing MTD, consistent with it being an inflammation biomarker. 10,12 Major increases in serum AFP, the rate of PVT and the rate of multifocality were found around a 5 cm MTD pivot point.…”
Section: Discussionmentioning
confidence: 81%